PENDEKATAN PERSONAL DALAM METODE PEMBELAJARAN AL-QURAN UNTUK SISWA YANG LEMAH DALAM BELAJAR DI MADRASAH TSANAWIYAH SWASTA JAUHARUL IMAN DESA SENAUNG KECAMATAN JAMBI LUAR KOTA KABUPATEN MUARO JAMBI - Hasbi, Muhammad; Thontawi, M. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the implementation of a personal approach in Qur'an learning methods for students with learning difficulties at MTs Jauharul Iman. This research used a qualitative method with data collection techniques including observation, interviews, and documentation. The results showed that the personal approach was implemented through special attention, adjustment of learning methods, and intensive guidance based on each student's abilities. This approach was proven to help improve the motivation and Qur'an reading skills of students who previously experienced learning difficulties. However, challenges were found in its implementation, such as limited teacher time, significant differences in student abilities, and lack of confidence among some students who received special attention.